2002
DOI: 10.1007/s00402-001-0369-0
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia and dyspnea due to an anterior cervical osteophyte

Abstract: Hypertrophic anterior cervical osteophytes have been reported as a cause of dysphagia, with about 100 cases described in the literature; on the other hand, chronic or acute dyspnea due to edema of the laryngeal inlet or bilateral vocal cord adduction-fixation is rare. We report a 57-year-old patient with a 2-year history of dysphagia and episodic dyspnea, who suffered sudden, severe respiratory distress necessitating emergency tracheotomy. A voluminous anterior cervical osteophyte at the C5 level was diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 0 publications
1
35
0
1
Order By: Relevance
“…Postulated explanations for the dysphagia caused by HACO include mechanical compression causing esophageal obstruction, periesophagitis and peripharyngitis, fibrosis and adhesions with fixation of the esophagus, cricopharyngeal spasm triggered by pressure on the esophagus, impaired epiglottic motility, and distortion of the larynx or the laryngeal cartilages [10,12,13,25,27,[30][31][32]. In our case, dynamic videofluoroscopy showed a displacement of the pharyngeal lumen anteriorly by HACO.…”
Section: Pathogenesis Of Dysphagiamentioning
confidence: 55%
See 2 more Smart Citations
“…Postulated explanations for the dysphagia caused by HACO include mechanical compression causing esophageal obstruction, periesophagitis and peripharyngitis, fibrosis and adhesions with fixation of the esophagus, cricopharyngeal spasm triggered by pressure on the esophagus, impaired epiglottic motility, and distortion of the larynx or the laryngeal cartilages [10,12,13,25,27,[30][31][32]. In our case, dynamic videofluoroscopy showed a displacement of the pharyngeal lumen anteriorly by HACO.…”
Section: Pathogenesis Of Dysphagiamentioning
confidence: 55%
“…Similarly, iatrogenic manipulations such as tracheal intubation and respiratory infections may increase tissue inflammation and may complicate moderate symptoms [8,12,19]. Unilateral or bilateral vocal fold hypomobility or immobility has been reported in only 14 cases of HACO with dyspnea [7,9,10,22,[24][25][26]29]. The exact mechanism of vocal fold immobility remains unclear, although different hypotheses have been discussed: paresis of terminal laryngeal nerve fibers, trauma to the posteriorly located cricoarytenoid muscles (lateral and posterior), and direct involvement of the cricoarytenoid joint.…”
Section: Pathogenesis Of Dyspneamentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, previously reported pathology of dysphasia due to anteriorly protruding deformity of the cervical spine can be classified into OALL [1,5,16] and osteophytosis related to cervical osteoarthritis [5,6,12,13,15,16]. In the present study, large osteophyte at a still mobile intervertebral segment in a patient with OALL and DISH, suggesting that the osteophyte can be potentially an immature form of the OALL, were subjected for analyses.…”
Section: Discussionmentioning
confidence: 89%
“…Clinical studies have shown that 17-28% of patients with DISH manifested symptoms of dysphagia due to cervical osteophytes [6,9]. Conservative treatment has been indicated for the initial management of these cases [2,16].…”
Section: Introductionmentioning
confidence: 99%